2017
DOI: 10.1038/ncb3477
|View full text |Cite
|
Sign up to set email alerts
|

A Twist2-dependent progenitor cell contributes to adult skeletal muscle

Abstract: Skeletal muscle possesses remarkable regenerative potential due to satellite cells, an injury-responsive stem cell population located beneath the muscle basal lamina that expresses Pax7. By lineage tracing of progenitor cells expressing the Twist2 (Tw2) transcription factor in mice, we discovered a myogenic lineage that resides outside the basal lamina of adult skeletal muscle. Tw2+ progenitors are molecularly and anatomically distinct from satellite cells, are highly myogenic in vitro, and can fuse with thems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
163
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(177 citation statements)
references
References 54 publications
14
163
0
Order By: Relevance
“…9). Additionally, some genes involved in the smooth muscle maturation and skeletal myogenesis, as reported in previous studies (31)(32)(33)(34)(35)(36), were also found to be differentially expressed in CK14-Cre;Shh fl/fl mutant mice ( Fig. 9).…”
Section: Discussionsupporting
confidence: 78%
“…9). Additionally, some genes involved in the smooth muscle maturation and skeletal myogenesis, as reported in previous studies (31)(32)(33)(34)(35)(36), were also found to be differentially expressed in CK14-Cre;Shh fl/fl mutant mice ( Fig. 9).…”
Section: Discussionsupporting
confidence: 78%
“…This may be the precipitating alteration that impacts normal EOM formation, as neural crest cells are crucial for normal EOM development through their expression of retinoic acid [37, 38]. Interestingly, a recent report has shown a Twist1-positive mesenchymal cell population in skeletal muscle which can contribute to the regeneration and maintenance of type II fibers [39]. The potential role of these cells in the EOMs has yet to be determined.…”
Section: Eom Regenerative Cell Populationsmentioning
confidence: 99%
“…In addition to these cell populations, mesenchymal cells that express the transcription factor Twist2 were recently reported to act as myogenic progenitors, however, with selective type IIb fibre-differentiation potential (Liu et al, 2017). PICs (Pw1+ Interstitial Cells) were also reported to engraft efficiently and contribute to myofibre regeneration following intramuscular injection (Mitchell et al, 2010).…”
Section: Cellular Regulators Of Muscle Repair and Their Regenerative mentioning
confidence: 99%